Atroposelective carbonylation of aryl iodides with amides: facile synthesis of enantioenriched cyclic and acyclic amides. Issue 21 (13th September 2021) - Chen, Li-Ping; Chen, Jiang-Fei; Zhang, Yu-Jiao; He, Xing-Yi; Han, Ya-Fei; Xiao, Yu-Ting; Lv, Gui-Fen; Lu, Xin; Teng, Fan; Sun, Qing; Li, Jin-Heng
Abstract : An unprecedented palladium-catalyzed asymmetric carbonylation of ArI with carbon monoxide (CO) to expand a class of atroposelective cyclic and acyclic amides in good yields with high enantioselectivities has been reported. Abstract : Axially chiral cyclic and acyclic amides are frequently found in natural products and bioactive molecules, but catalytic asymmetric synthesis of these atropisomers with high efficiency has been a formidable challenge. We herein describe an unprecedented palladium-catalyzed asymmetric carbonylation of ArI with carbon monoxide (CO) to atroposelectively expand a class of 2-arylisoindoline-1, 3-diones and N -acetyl- N -phenyl benzamides in good yields with high enantioselectivities, which represents the first example that inlays the carbonyl group in the axially chiral amides via a carbonylative reaction. Besides, a pair of enantiomorphous isomers of 2-arylisoindoline-1, 3-diones can be elegantly obtained by controlling substituents at different positions.